Region i badania regionalne w perspektywie socjologii - Kwilecki, Andrzej (Wydział Prawa i Administracji UAM, 1992)
The author points to the diversity of conceptions of distinguishing regions along various criteria: geographical, economic, ethnographic, administrative, self-governmental and sociological. All those conceptions are based on distinguishing local and cultural communities, in various ways arranged into larger regional groups. It is connected with distinguishing the "homeland" ("Heimat") along the "ideological motherland" and with the development of regional research on culture of particular regions. Regional research are subject to deep transformations as to their character and functions in connection with an increased social mobility, and, in effect, in connection with the blurring of distinct features of traditional, historical and ethnographic regions. Regional research is of particular importance in view of t he present works on new administrative division of t h e state, in correspondance with the changed social structures.
The region and régional research in sociological perspective